Bedside reduction of gastroschisis: A feasible option - Deepak, J; Aravind, K L; Jadhav, Vinay; Shankar, Gowri; Narendrababu, M (Indian Journal of Child Health, 2016)
Background: Gastroschisis is a common neonatal malformation, with an incidence of 0.4-3 per 10,000 live births worldwide. Objective: This study was planned to assess the feasibility of bedside reduction of gastroschisis (BRG) in the neonatal intensive care unit (NICU) at our institution. Materials and Methods: Retrospective analysis of newborns with gastroschisis managed at our institution between September 2008 and May 2013. Initial bedside reduction in NICU was attempted in all the neonates procedure was done under local anesthesia. Incision was extended transversely on the lateral aspect when required. Gradual reduction of bowel loops done with monitoring of parameters. Complete abdominal wall closure in multiple layers/skin closure only was done based on intra-abdominal tension. The final outcome was recorded. Results: During the study period of 60-month, 10 children were treated for gastroschisis at our institution. The sex ratio among them was 8:2 in favor of males. The average age was 23 h (range: 4-72 h). The average birth weight of the babies was 2290 g (range: 1700-2600 g). Six patients were in the high-risk group and 4 in the low-risk group. The BRG was successful in 7 patients and a silo was placed in 3 patients who did not tolerate BRG. General anesthesia was required in 3 patients only for subsequent repair. The overall survival was 70%. Conclusion: BRG is a feasible and safe option. Selective use of silo, gradual staged bowel reduction, and delayed primary closure of the defect can be done on the bedside when attempted BRG is unsuccessful.